Pengaruh Audit Internal dan Good Corporate Governance Terhadap Kinerja Keuangan Perbankan Syariah Indonesia - Nur Isra Laili; Maya Richmayati; Elminaliya Sandra (Komunitas Dosen Indonesia, 2024)
This research aims to analyze the effects of internal auditing and effective corporate governance on the financial performance of Islamic banks in Indonesia. The study utilized financial data from the annual reports of Islamic banks registered with the Financial Services Authority (OJK) from 2019 to 2021. Employing purposive sampling, the study gathered data from 33 observations. The analysis was conducted using multiple regression to test the research hypotheses. The results demonstrate that internal audit activities, combined with governance structures including the board of directors, the audit committee, and the Sharia supervisory board, significantly influence the banks' return on assets (ROA). In particular, the internal audit functions and the board of directors were found to have a notable impact on the financial outcomes. However, the audit committee and the Sharia supervisory board did not exhibit a statistically significant effect. Correlation analyses further indicate significant relationships between return on equity and the examined variables: internal audit (X1), board of directors (X2), audit committee (X3), and Sharia supervisory board (X4). The model's coefficient of determination (R²) is 0.328, suggesting it accounts for 32.8% of the variance in financial performance, with the remainder influenced by unexamined factors.